IDENTIFICATION OF SCHOOL EXAM RESULT AT SMPN 05 MUKO-MUKO IN THE LAST 5 YEARS ON NATURAL SCIENCE MATERIAL - Apriliani Mersa Putri; Sopiah Citrawati; Tike Seprianti; Ahmad Walid (Universitas Bhinneka PGRI, 2023)
The purpose of this study was to identify the results of the science class IX school exams, which were held at SMPN 05 Muko-Muko for the last 5 years starting from 2017-2021. In this study, the researcher used a descriptive method with a qualitative approach, where the data collection technique used was observation, interviews. Data collection was carried out on November 29, 2022. Data analysis techniques were obtained from student school exams, the number of students who took the exam in the last 5 years, and the year the school exam was held. then analyzed and presented in the form of tables and graphs. The results obtained from interviews with related teachers show that the percentage of school exam results at SMPN 05 Muko-Muko has increased. Which in 2017 amounted to (42.44%), 2018 amounted to (45.05%), 2019 amounted to (70%), 2020 (70%) and in 2021 amounted to (70%).